A família Callichthyidae compreende um grupo monofilético bem corroborado, dividida em duas subfamílias: Corydoradinae e Callichthyinae - Spadella, Maria A.; Desan, Simone P.; Henriques, Teresa C. B. P. O.; Oliveira, Claudio [UNESP] (FapUNIFESP (SciELO), 2017)
Callichthyidae comprises a well-corroborated monophyletic group divided into two subfamilies: Corydoradinae and Callichthyinae. A recent proposal, based on molecular data, suggests that Corydoradinae is composed by nine monophyletic lineages, possibly genera. The species pertaining to those lineages have extensive modification in the size of genome, including diploid, tetraploid and octoploid species. Considering the occurrence of these monophyletic lineages and that the variations in DNA content may imply in significant alterations on the structure of spermatozoa, this study analyzed the morphology of the male reproductive system and the morphometry of the head of the spermatozoa of representatives of the nine lineages of Corydoradinae, seeking for particular characteristics of each lineage. Morphological data revealed a high intra-lineage variation, larger than that observed among species of different lineages. In contrast, morphometric data obtained for eight out of the nine lineages, revealed large congruency with the hypothesis that Corydoradinae is composed by different lineages. These results demonstrate that there is a correlation among variations in DNA content and the size of the spermatozoon head, thus providing additional subsides for the definition of the Corydoradinae lineages.
Variation in male reproductive system characters in corydoradinae (Loricarioidei: Callichthyidae) reflects the occurrence of different lineages in this subfamily
Keywords: Monophyly; Morphometry; Spermatozoa; Variations in DNA